Basic Questions on Truth - Weingartner, P. author. aut Link
X, 230 p.
Keywords: The task of the book is not to give a survey of the main theories on truth found in the literature. There are several books available which do this: The one of David for Deflationist (and Disquotational) Theories of Truth; that of Chapuis for Revision Theories of Truth; that of Kirkham for Correspondence Theories and several others; that ofRescher for Coherence Theories of Truth. Moreover the book is not an analy sis just of Tar ski's theory, like that of Moreno or the respective chapters in Kirkham, though Tarski's theory plays an important role in the whole work presented. The task of the book is to give a detailed answer to some basic questions on truth which have been perennial problems through the centuries and are still discussed today. The answer is given in the light of our knowledge today and with the help of modem logic. But the book explicitly aims at connecting recent problems with re lated ones in the whole history of philosophy. The method to incorporate important philosophers of the tradition into the analysis is that of disputation, i. e. of putting some of their main thesis into objections or counterobjections pro or contra a posi tive answer to the respective question. After the pros and cons are given a detailed answer to the question is proposed and finally commentaries and corrections are given to the objections and counterobjections in the light of the proposed answer.